Antidiabetic activity of Helicteres angustifolia root. (2nd June 2016) - Hu, Xuansheng; Cheng, Delin; Zhang, Zhenya
Abstract: Context The root of Helicteres angustifolia L. (Sterculiaceae) has been used as folk herbal drug to treat cancer, bacterial infections, inflammatory, and flu in China. However, there is no report on its antidiabetic activity. Objective This study evaluates the antidiabetic activity of ethanol extract from H. angustifolia root. Materials and methods The promoting effect of H. angustifolia root ethanol extract (25, 50, and 100 μg/mL) on glucose uptake was evaluated using HepG2 cell, differentiated C2C12 myotubes, and differentiated 3T3-L1 adipocytes. The antidiabetic activity of the extract was assessed in vivo using STZ-induced diabetic rats by orally administration of the extract (200 and 400 mg/kg b.w.) once per day for 28 d. Blood glucose, TG, TC, TP, HDL-C, UA, BUN, AST, ALT, insulin, and HOMA-IR were analyzed. Results The results showed that the extract increased glucose uptake in C2C12 myotubes and 3T3-L1 adipocytes with an IC50 value of 79.95 and 135.96 μg/mL, respectively. And about 12%, 19%, and 10% ( p < 0.05) in HepG2 cells when compared with the control at the concentration of 25, 50, and 100 μg/mL, respectively. After 28 days' treatment with the extract, significant reduction was observed in blood glucose, HOMA-IR, TC, TG, UA, BUN, AST, and ALT levels, while the levels of TP and HDL cholesterol increased. Discussion and conclusion These results suggest that H. angustifolia root ethanol extract possess potent antidiabetic activity, which is the first report on antidiabetic activity of this plant.